2018
DOI: 10.1002/app.47209
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of heavy metal ion adsorption using electrospun polyacrylonitrile nanofibers loaded with ZnO nanoparticles

Abstract: This article describes the adsorption and tensile behavior of electrospun polyacrylonitrile (PAN) nanofiber mats loaded with different amounts of ZnO [0.5, 1.0, 2.0, and 5.0 wt%] nanoparticles. X‐ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transforminfrared (FTIR) spectroscopy, and thermal gravimetric analysis (TGA) were utilized to characterize the resulting composite nanofibers. Microscopic investigations revealed that the increase in surface roughness and diameter of the electrospun P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 70 publications
0
20
2
Order By: Relevance
“…The bilayer nanofiber mats composed of PAN/MO (PAN/ZnO and PAN/TiO 2 ) and CS were fabricated using electrospinning. The first layer of electrospun PAN mixed with 2.0 wt % ZnO or PAN mixed with 2.0 wt % and 5.0 wt % TiO 2 were prepared following our previously published procedure [9,25]. It was found that as the concentration increases to more than these percentages, the adsorption decreases.…”
Section: Preparation Of Electrospun Bilayer Nanofiber Matsmentioning
confidence: 99%
See 3 more Smart Citations
“…The bilayer nanofiber mats composed of PAN/MO (PAN/ZnO and PAN/TiO 2 ) and CS were fabricated using electrospinning. The first layer of electrospun PAN mixed with 2.0 wt % ZnO or PAN mixed with 2.0 wt % and 5.0 wt % TiO 2 were prepared following our previously published procedure [9,25]. It was found that as the concentration increases to more than these percentages, the adsorption decreases.…”
Section: Preparation Of Electrospun Bilayer Nanofiber Matsmentioning
confidence: 99%
“…2.0 wt % of ZnO nanoparticles was used for lead and cadmium adsorption experiments, 2.0 and 5.0 wt % of TiO 2 nanoparticles were used for lead and cadmium adsorption experiments, respectively. These amounts were selected based on our previous study, as they provided the most favorable removal percentages against the metal ions [9,25]. For the purpose of simplicity and clarity, the weight percentages of ZnO and TiO 2 will not be written explicitly in the labels of the bilayer mats (e.g., PAN/TiO 2 (2 wt %)-CS will be referred to as PAN/TiO 2 -CS only).…”
Section: Preparation Of Electrospun Bilayer Nanofiber Matsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peter et al reported arsenate and chromate adsorption via a polymer–iron oxide nanofiber (NF) filter . Alharbi et al fabricated polyacrylonitrile (PAN)/ZnO composite NFs to adsorb Pb(II) and Cd(II) ions …”
Section: Introductionmentioning
confidence: 99%